Localized heating with a photothermal polydopamine coating facilitates a novel membrane distillation process. Issue 39 (23rd August 2018) - Wu, Xuanhao; Jiang, Qisheng; Ghim, Deoukchen; Singamaneni, Srikanth; Jun, Young-Shin
Abstract : This study demonstrates a simple, stable, and scalable polydopamine (PDA) coated PVDF membrane for highly efficient solar-driven membrane distillation. Abstract : Solar-driven membrane distillation using photothermal membranes is of considerable interest for future water desalination systems. However, the low energy efficiency, complex synthesis, and instability of current photothermal materials hinder their further development and practicability. In this study, for the first time, we demonstrate a simple, stable, and scalable polydopamine (PDA)-coated polyvinylidene fluoride (PVDF) membrane for highly efficient solar-driven membrane distillation (MD). Our membrane shows the best energy efficiency among existing photothermal MD membranes (45%) and the highest water flux (0.49 kg m −2 h −1 ) using a direct contact membrane distillation (DCMD) system under 0.75 kW m −2 solar irradiation. Such a performance was facilitated by the PDA coating, whose broad light absorption and outstanding photothermal conversion properties enable higher transmembrane temperature and increased driving force for vapor transport. In addition, the excellent hydrophobicity achieved by fluoro-silanization gives the membrane great wetting resistance and high salt rejection. More importantly, the robustness of our membrane, stemming from the excellent underwater adhesion of the PDA, makes the composite membrane an outstanding candidate for real-world applications.